YAKYM YAREMA: TYPOLOGY OF A TEACHER AT THE PEDAGOGY TYPOLOGY OF THE FIRST HALF OF 20TH CENTURY - Zveryuk, Ruslan (Educological discourse, 2018)
The article analyses the content of methodological, psychological and pedagogical approaches of Yakym Yarema towards the analysis of pedagogical work, on the basis of the research of the content of the scientists' own ideas, written in "The psychology of a teacher's rank - typology" 1935. The content of the notion "knowledge" as a professional validity, general methodology of a research that corresponds to the integrated principles of the life philosophy and Lviv-Warsaw School of Philosophy, used by the researcher, is studied out by using the method of comparative analysis. The research of the basis of professional psychology, done by Yakym Yarema, "the object of which is a human" gave the possibility to compare the limits of pedagogical professionalism in about the century time period. The acmeological approaches towards the characterizing of the pedagogues types in the work of Ya. Yarema realizes owing to the combination of analysis of cultural and psychological types of a human (humanitarian psychology and ethics of a personality), typology of a teachers in the frames of educational potential of types (psychological analysis of a personality of a teacher-educator) and own scientific vision of historical and pedagogical stage. It is determined that the type of personality, according to Ya. Yarema, is the category of cultural and historical order, in relation with its phenomenon, changes occur not only key characteristics of types, but also the priorities of either types towards the relative type of pedagogics. The scientist mentioned the transference from sentimental sensual mood pedagogics, for which the most corresponding type was socio-aesthetic and dynamic-energetic (energetic-nomocratic), which requires power-economic type. The results of the research of the work of Ya. Yarema can be used in the modern conditions as the methodology of professional-pedagogical competences formation. The key conclusions are the following: pedagogical professionalism is a dynamic category that needs the study on different stages of cultural and historical development of a society; pedagogical science, according to the researches of Ya. Yarema, develops within the frames with philosophy and psychology; the notion of a child, type of pedagogue and type of pedagogics are closely interconnected, and thus, their study, as well as a change, should be proportional.